Genomic and phylogenetic analysis of Argentinian Equid Herpesvirus 1 strains - Martín Ocampos, Giselle Paula (2009)
Equid Herpesvirus 1 (EHV-1) has long been causally implicated in the occurrence of abortion, neonatal death, respiratory disease, and neurological disorders in horses. This study analyzed for the first time the characteristics of the genomic section of Argentinian EHV-1 strains and reconstructed the phylogeny in order to establish their origin. The phylogenetic dataset included 22 Argentinian strains and four additional reference strains isolated in other countries. The intergenic region between ORF 62 and ORF 63 was amplified by PCR and sequenced. The phylogenetic analysis carried out by parsimony algorithms showed that six of the Argentinian strains had the same origin as British and Japanese strains. The mapping of symptoms caused by EHV-1 suggested that neonatal disease developed through convergent evolution, which would constitute an adaptation mechanism of the virus. This study constitutes the first analysis carried out in South-American strains that establishes the phylogenetic relationship between Argentinian strains and rebuilds the evolutionary history of symptoms. This study focuses on a very important aspect of evolution of Herpesviridae infecting perissodactyls and attempts to shed light on the evolution of symptoms, an issue of high clinical interest.